Occupational therapists' perceptions of habits based on their professional experiences. (4th March 2017) - Mårtensson, Lena; Archenholtz, Birgitha
Abstract: Background: Habits are building blocks for occupation. If they are not explicitly approached, a vital aspect of occupation may be left out. Knowledge is lacking about how habits are understood and approached in occupational therapy practice. Aim: To explore occupational therapists' perceptions of habits based on their professional experiences. Material and methods: A qualitative design with a focus group methodology was used. The qualitative data analysis was based on five focus group discussions, including 34 occupational therapists. Results: An overarching theme, 'the complexity of habits, ' representing the occupational therapists' perception of habits, covers the content of three categories: 'reflecting contradictoriness, ' including different forms of ambiguity that characterize habits, 'reflecting identity and security', that emphasize the meaning of habits for identity and structure in everyday life, and 'reflecting context and society', comprising perceptions of habits related to the life situation, time and social patterns and environment. Conclusions: The occupational therapists' perceptions gave a picture of habits as complex systems. Based on the findings, the therapeutic modes used when approaching clients' habits should involve more explicit attention to habits and the inclusion of the client's entire context.